Differences in IgG Responses against Infection phase Related Mycobacterium Tuberculosis (Mtb) Specific Antigens in Individuals Exposed or not to Mtb correlate with control of TB Infection and Progression (2017)
ABSTRACT: Tuberculosis (TB) occurs in only 3e10% of Mycobacterium tuberculosis (Mtb) infected individuals, suggesting that natural immunity can contain Mtb infection, although this remains poorly understood. Next to T-cells, a potentially protective role for B-cells and antibodies has emerged recently. However, the Mtb antigens involved remain ill-defined. Here, we investigated in a TB-endemic setting IgG levels against 15 Mtb antigens, representing various phases of Mtb infection and known to be potent human T-cell antigens. IgG levels against ESAT6/CFP10, Rv0440, Rv0867c, Rv1737c, Rv2029c, Rv2215, Rv2389c, Rv3616c and Mtb purified protein derivative (PPD) were higher in TB patients than in endemic and non-endemic controls. The only exception was Rv1733c that was preferentially recognized by antibodies from endemic controls compared to TB patients and non-endemic controls, suggesting a potential correlation with control of TB infection and progression. In patients, IgG levels against Ag85B and Rv2029c correlated with Mtb loads, while immunoglobulins against Rv0440 differed between genders. Our results support the potential role of certain Mtb antigen-(Rv1733c) specific antibodies in the control of TB infection and progression, while other Mtb antigen-specific antibodies correlate with TB disease activity and bacillary loads. The findings for Rv1733c agree with previous T-cell results and have implications for including antibody-mediated immunity in designing new strategies to control TB.